Ecomorphological forms in Dwarf Chameleons (Bradypodion): assessment of functional morphology and gene flow across spatially adjacent habitat types - Potgieter, Daniel Francois (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.